Implementation of the world health organization surgical safety checklist at a university hospital in Thailand - Kasatpibal N. (2014)
Background: Compliance with the World Health Organization (WHO) surgical safety checklist may reduce preventable adverse events. However, compliance may be difficult to implement in Thailand. This study was conducted to examine compliance with the WHO checklist at a Thai university hospital. Methods: A descriptive study was conducted among 4,340 patients undergoing surgery in nine departments from March to August 2009. The compliance rates were computed. Results: The highest compliance rate (91.4%) during the sign-in period was with patients' confirmation of their identity, operative site, procedure, and consent. However, only 19.4% of the surgical sites were marked. In the time-out period, surgical teams had introduced themselves by name and role in 79% of the operations; and in 95.7% of the cases, the patient's name, the incision site, and the procedure had been confirmed. Antibiotic prophylaxis had been given within 60 min before the incision in 71% of the cases. For 83% of the operations, the surgeons reviewed crucial events whereas only 78.4% were reviewed by the anesthetists. Sterility had been confirmed by the operating room nurses for every patient, but the essential imaging was displayed at a rate of only 64.4%. In the sign-out period, nurses correctly confirmed the name of the procedure orally in 99.5% of the cases. Instrument, sponge, and needle counts were completed and the specimen was labeled in most cases, 96.8% and 97.6%, respectively. Equipment-related problems were identified in 4.4% of the cases, and 100% of them were addressed. The surgeon, anesthetist, and nurse reviewed the key concerns for recovery and management of the patient at the rate of 85.1%. Conclusions: The WHO checklist can be implemented in a developing country. However, compliance with some items was extremely low, reflecting different work patterns and cultural norms. Additional education and enforcement of checklist use is needed to improve compliance. © 2012, Mary Ann Liebert, Inc.